Risk of second primary cancer after Hodgkin's disease in patients in the British National Lymphoma Investigation: relationships to host factors, histology and stage of Hodgkin's disease, and splenectomy. - Swerdlow, A. J. (Nature Publishing Group, 1993)
The risks of second primary cancer were analysed in 2846 patients with Hodgkin's disease treated within the British National Lymphoma Investigation during 1970-87. The relative risk (RR) of leukaemia was significantly greater in women (RR = 30.1; 95% confidence limits (CL) 13.0-59.5) than in men (RR = 10.9; 95% CL 4.7-21.5), and showed a significant trend of greater risk with younger age at first treatment (P < 0.001). The relative risk of solid cancers was similar between the sexes, but again significantly greater at young than at older ages of first treatment (P < 0.01). Non-Hodgkin's lymphoma relative risks, although not related to sex or age, were significantly related to histology of the original Hodgkin's disease, and were greatest after lymphocyte predominant Hodgkin's disease (RR = 55.6; 95% CL 18.0-129.7). The relative risk of second cancers did not vary significantly according to whether or not splenectomy had been performed. Leukaemia risk was non-significantly greater after splenectomy than with no splenectomy, which accorded with previous evidence of a modest increased risk associated with this operation. If the greater relative risk of solid second cancers after treatment at young than at older ages persists with longer follow-up, the incidence rates of these second primaries in patients treated young for Hodgkin's disease will become very substantial as they age. This emphasises the need to maintain long-term follow-up surveillance of young Hodgkin's disease patients apparently cured of their disease, and to continue to develop new less carcinogenic treatment regimens.